La légende Caravage. Vie et œuvre de l’artiste, entre fantasmes et réalités - Natacha Aprile (Les Cahiers de Framespa)
Revealing the truth about the tormented life of Caravaggio has been one of the main research topics of the early 20th century. But, as far his homosexuality is concerned, information is missing. His sexuality is still perceived as rumors, widespread by his rivals. Despite the testimony left in the archives, Caravaggio’s homosexuality is still ignored or understated. Studying homosexuality of famous personalities is complex and raises a lot of objections. Is studying art through the queer prism still possible despite the general reluctance? Based on this observation, this research will analyze the homophile network of Caravaggio, and among them, the cardinal Del Monte, one of the most important patrons of the painter and a well-known homosexual.